Room-temperature autonomous self-healing glassy polymers with hyperbranched structure - Wang, Hao (Proc Natl Acad Sci U S A, 2020)
Glassy polymers are extremely difficult to self-heal below their glass transition temperature (T(g)) due to the frozen molecules. Here, we fabricate a series of randomly hyperbranched polymers (RHP) with high density of multiple hydrogen bonds, which show T(g) up to 49 °C and storage modulus up to 2.7 GPa. We reveal that the hyperbranched structure not only allows the external branch units and terminals of the molecules to have a high degree of mobility in the glassy state, but also leads to the coexistence of “free” and associated complementary moieties of hydrogen bonds. The free complementary moieties can exchange with the associated hydrogen bonds, enabling network reconfiguration in the glassy polymer. As a result, the RHP shows amazing instantaneous self-healing with recovered tensile strength up to 5.5 MPa within 1 min, and the self-healing efficiency increases with contacting time at room temperature without the intervention of external stimuli.